The Role of a Companion Banner and Sponsorship Transparency in Recognizing and Evaluating Article-style Native Advertising. Issue 1 (August 2018) - Campbell, Colin; Evans, Nathaniel J.
Native advertising is a relatively new form of online advertising that matches the format of surrounding non-advertising content. The fact that native advertising blends into its context risks deceiving consumers who may be unaware the content they are viewing is actually advertising. Article-style native advertising, a native ad form that mimics the style of online news articles, is particularly concerning since consumers may not expect advertising to appear in such a format. Such concern is supported by research finding low efficacy of traditional disclosures on article-style native advertisements. We investigate a novel means of increasing ad recognition through the use of companion banner advertising. Across two experiments we demonstrate that inclusion of a companion banner boosts consumer recognition of the paid nature of article-style native advertising to the same degree as a traditional disclosure. In both cases we also find that the negative reactions caused by ad recognition are muted when a native ad is perceived as having higher sponsorship transparency. These effects occur for both familiar and unfamiliar brands. Taken together, results not only detail the efficacy of a new means of achieving adequate disclosure, but also develop greater understanding of how consumers respond to article-style native advertising.